Towards a Model of Effective Group Facilitation - Wardale, Dorothy (Emerald Group Publishing Ltd., 2013)
Purpose – This paper aims to report on research into managers’ and facilitators’ perceptions of effective facilitation.Design/methodology/approach – A total of 20 managers from across five industry sectors, and 20 facilitators from larger organisations or working as consultants, were interviewed in-depth regarding stories of effective and wholly or partially ineffective facilitation experiences. These stories are analysed within a constructivist-interpretivist paradigm.Findings – Four stages important to facilitation are identified: Preparation, Event, Satisfactory Outcomes and Transfer. Strategies and considerations are evident in the first three stages but poorly discussed and under-utilised strategies in the last.Research limitations/implications – Further research is suggested to identify strategies for implementing outcomes; consider the contribution internal facilitators can make to the facilitation process; appreciate of the context within which the facilitation takes place; and the impact of organisational size and culture of the facilitation process.Practical implications – Facilitation is likely to be more effective if facilitators share a common language with the participant group; are conscious of the Transfer stage through-out the process; and work to ensure affective, as well as effective, outcomes. Managers may also consider training, empowering and utilising their internal facilitators to a greater extent, in recognition of the value-adding their knowledge about the organisation brings.Originality/value – This paper adds a multi-dimensional framework of facilitation to the empirical evidence for academics and practitioners working in the areas of facilitation and group effectiveness.